The Impact of Urbanization on Women’s Roles and Family Dynamics - Achieng Wanjiku; Njeri Akinyi; Chebet Adhiambo (Journal Social Humanity Perspective, 2026)
Urbanization has profoundly influenced social, economic, and familial structures in sub-Saharan Africa, yet its impact on women’s roles within households remains underexplored. This qualitative study investigates how urbanization has reshaped the role of women in families in Nairobi, Kenya, focusing on economic participation, decision-making authority, and the persistence of traditional domestic responsibilities. Using a phenomenological approach, data were collected through in-depth semi-structured interviews and participant observations with 18 women across diverse socioeconomic backgrounds. Thematic analysis revealed that urbanization has expanded women’s economic roles, enabling them to contribute significantly to household income and assert greater influence in family decision-making. Simultaneously, traditional expectations regarding domestic labor persist, resulting in a dual burden that challenges women’s capacity to balance professional and domestic responsibilities. Male partners exhibit varying responses to these shifts, ranging from support and adaptation to resistance and negotiation, highlighting the contested nature of gender power dynamics within urban households. The study underscores that families operate as micro-organizational systems, wherein role allocation, resource management, and decision-making processes mirror principles of organizational management. These findings carry significant implications for policymakers, organizational leaders, and urban planners, emphasizing the need for holistic interventions that integrate economic empowerment, domestic workload redistribution, and socio-cultural transformation to achieve genuine gender equity. By situating household dynamics within the broader urban economic and social context, this study provides critical insights into the interplay between urbanization and the evolving roles of women, offering a framework for understanding and supporting equitable family structures in rapidly urbanizing cities.